Antenatal screening for Down's syndrome, trisomy 18, and trisomy 13: Reporting a single screening result for all three. (June 2015) - Bestwick, Jonathan P; Wald, Nicholas J
Objective: To compare the performance of antenatal screening for Down's syndrome (DS), trisomy 18 (T18), and trisomy 13 (T13) using a single risk of being affected by one of the three disorders, with the performance using separate risks for each disorder. Methods: Screening performance was estimated using Monte Carlo simulation based on published parameters for the Integrated, Combined, and Quadruple tests. Detection rates (DRs) were calculated using a single risk and separate risks for each disorder at given false-positive rates (FPRs). Results: With separate risks, using a 3% DS test FPR and 0.2% FPRs for the T18 and T13 tests, the overall FPRs for the Integrated and Combined tests are both 3.3%. For the same overall FPR (3.3%), the use of a single risk with the Integrated test increases the T13 DR from 76% to 82%, with unchanged DS and T18 DRs (94% and 92% respectively). With the Combined test, it increases the T13 and T18 DRs (from 89% to 91% and 77% to 81% respectively), with unchanged DS DR (85%). With separate risks, using a 5% DS test FPR and 0.2% FPRs for the T18 and T13 tests, the overall FPR for the Quadruple test is 5.4%. For the same overall FPR (5.4%), the use of a single risk increases the T18 DR from 61% to 67% with unchanged DS and T13 DRs (87% and 33% respectively). Conclusions: Reporting a single risk estimate for the three disorders is less confusing than reporting separate risks and can yield the same or better screening performance.